2001
DOI: 10.1001/archotol.127.4.401
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Otalgia in an Adult Population

Abstract: We suggest that after ruling out otorhinolaryngologic infectious diseases and temporomandibular disorder in patients with secondary otalgia, the next step is to explore the frequency of stress symptoms, bruxism, and recurrent neck pain. Furthermore, women and men may need a different approach in diagnostics of secondary otalgia. By diagnosing and treating these predictors of otalgia, it may be possible to reach a more successful outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 14 publications
(20 reference statements)
3
22
0
5
Order By: Relevance
“…The current study observed that 59.2% of the participants reported to have bruxed their teeth during working hours. Prevalence reported in our study is higher when compared to bruxism reported for other work forces [6, 7] and adult population [8]. Diurnal bruxism was recorded based on self-reports by the participants and was diagnosed based on self-reported awareness of the habit since there are no standardized diagnostic criteria.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The current study observed that 59.2% of the participants reported to have bruxed their teeth during working hours. Prevalence reported in our study is higher when compared to bruxism reported for other work forces [6, 7] and adult population [8]. Diurnal bruxism was recorded based on self-reports by the participants and was diagnosed based on self-reported awareness of the habit since there are no standardized diagnostic criteria.…”
Section: Discussionmentioning
confidence: 59%
“…According to an investigation by Ahlberg et al [7] about 11% of media personnel reported to have bruxism. Kuttila et al [8] reported the occurrence of diurnal bruxism without symptoms in a population-based study to be 7.3%. …”
Section: Introductionmentioning
confidence: 99%
“…Ear pain was found more likely to be present in IHS migraineurs than in patients with other headache types (7). Otalgia patients also have been previously found to have headache more often than nonotalgia patients (8). Neither study related ear pain to headache mechanisms.…”
Section: Discussionmentioning
confidence: 85%
“…It is important to know that symptoms of the ear are not present in over 50% of the patients who express otic complaints such as retroauricular and/or preauricular pain, tinnitus, vertigo, hearing impairment, otic fullness, and ear popping sensations. (Gelb et al, 1959;Gelb & Tarte, 1975;Kuttila et al, 1999;Kuttila et al, 2001). Bernhardt et al, (2004) found a significant correlation between tinnitus and TMD, affirming that TMD might cause otologic symptoms.…”
Section: Introductionmentioning
confidence: 98%